Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.31274/itaa_proceedings-180814-380
|View full text |Cite
|
Sign up to set email alerts
|

Women's Motivations to Sew Clothing for Themselves

Abstract: Significance and purpose.A resurgence is currently happening in home sewing participation that includes a growing interest in personal garment sewing among women (Haider, 2015). These women are choosing to spend their leisure time sewing garments for themselves instead of buying in the age of inexpensive, fast fashion. It is important to understand these women's perceived benefits of sewing, related behaviors, and use of leisure time, as they operate outside of typical consumer culture. The purpose of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For security and privacy of participants, all audio recordings, interview transcripts, and data analysis were stored in a secured data cloud accessible by the researchers only. The interview guide (Appendix A) contained a mix of 15 open-ended questions modified from previous research [45]. Participants were asked about their process for engaging in fashion GLEPs, related maintenance skill set and resources, individual usership characteristics, and overall engagement with communities who practice garment life extension.…”
Section: Methodsmentioning
confidence: 99%
“…For security and privacy of participants, all audio recordings, interview transcripts, and data analysis were stored in a secured data cloud accessible by the researchers only. The interview guide (Appendix A) contained a mix of 15 open-ended questions modified from previous research [45]. Participants were asked about their process for engaging in fashion GLEPs, related maintenance skill set and resources, individual usership characteristics, and overall engagement with communities who practice garment life extension.…”
Section: Methodsmentioning
confidence: 99%
“…Valuing knowledge from the past is sometimes linked to feminism. Unlike the home sewers interviewed by Martindale (2017), several of these participants described themselves and their sewing as feminist. Expressing views common to third-wave feminists (Bain, 2016;Chansky, 2010;Stalp, 2015), some participants described their retro sewing as "subversive" because they use classic styles and traditional feminine pursuits (i.e., sewing) in a non-traditional way.…”
Section: Valuing the Past In The Presentmentioning
confidence: 99%
“…Sewing and DIY have always encapsulated feminist characteristics by allowing the participant to challenge social norms and define their own visual identity (Gordon, 2004;Hackney, 1999). Recent studies have identified sewing as having the same characteristics as third-wave feminism (Bain, 2016;Martindale, 2017). Retro style is also used as a form of empowerment; vintage enthusiasts and retro sewers have observed that their adoption of retro style leads to better treatment from men (Hirsch, 2010;Rogers, 2013).…”
Section: Individualistic Nostalgia Vs Collectivistic Nostalgiamentioning
confidence: 99%
“…Individuals today are encouraged to choose their clothing from industry-dictated selections characterized by fashionable colors, styles, fits, fabrics and brand names (Guy et al, 2001). Research has shown that sewing evolved from an economic necessity to a creative outlet (Martindale, 2017). Frustrated at being underrepresented and underserved in the fashion industry, consumers use their cultural capitalfashion knowledge, craftsmanship, and sewing skillsfor self-presentation: I experienced many years of body shaming, so being able to wear my own creations provided me with the courage to stand up for myself.…”
Section: Cultural Capitalmentioning
confidence: 99%